2010
DOI: 10.1002/mds.22963
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative power of different nonmotor signs in early Parkinson's disease. A case-control study

Abstract: The objective of this study was to evaluate the discriminative power of different nonmotor signs for early diagnosis of Parkinson's disease (PD). Thirty patients with PD with Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…44 Many parts of the visual system have been implicated as the cause for visual deficits, such as the retina, where thinning of the inner retinal nerve fiber layer and decreased dopamine concentration seem to mirror the loss of dopaminergic neurons in the basal ganglia. 2,45,46 Pattern electroretinogram studies in PD subjects have shown significant loss at midspatial frequencies of 4 cyc/deg, corroborating our findings. 47 With the addition of motion, both PD and control subjects improved their contrast sensitivity at low spatial frequencies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…44 Many parts of the visual system have been implicated as the cause for visual deficits, such as the retina, where thinning of the inner retinal nerve fiber layer and decreased dopamine concentration seem to mirror the loss of dopaminergic neurons in the basal ganglia. 2,45,46 Pattern electroretinogram studies in PD subjects have shown significant loss at midspatial frequencies of 4 cyc/deg, corroborating our findings. 47 With the addition of motion, both PD and control subjects improved their contrast sensitivity at low spatial frequencies.…”
Section: Discussionsupporting
confidence: 81%
“…It is critical for many daily activities 1 and is impaired in patients with neurodegenerative diseases such as Parkinson's disease. [2][3][4][5] Conventionally, contrast sensitivity has been measured in the laboratory as a function of an object's richness in texture, its spatial frequency. We define spatial contrast sensitivity as the ability to distinguish static stimuli, and spatiotemporal contrast sensitivity as the ability to detect moving stimuli while tracking them with smooth pursuit eye movements.…”
mentioning
confidence: 99%
“…Colour vision has been reported to be significantly impaired in patients with PD compared with controls,26 including among patients with early PD (≤3years since onset)27 and patients with de novo PD 28. Retinal dopamine levels have been found to be reduced in patients with PD 29.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, non-motor signs across six different domains were explored in patients with early motor PD. 39 Tests addressed visual deficits tested by color discrimination, contrast sensitivity, and spatial discrimination; olfactory function; sleep abnormalities by Parkinson's Disease Sleep Scale rating and documentation of loss of muscle atonia during REM sleep on polysomnography; dysautonomia as reported on two self-completed questionnaires; executive dysfunction; and depression.…”
Section: Clinical Detection Of Pre-motor Parkinson's Diseasementioning
confidence: 99%
“…Across all domains, patients with PD performed worse than the control group, with statistically significant differences in visual deficits, sleep abnormalities, hyposmia, dysautonomia, and depression; the most marked distinction between the test and control groups emerged in visual deficits, hyposmia, and dysautonomia. 39 By combining the results of the Farnsworth-Munsell color discrimination test and the non-motor symptom questionnaire (NMSQuest), the sensitivity and specificity for detection of PD peaked at 0.77, suggesting a relatively simple model for predicting PD.…”
Section: Clinical Detection Of Pre-motor Parkinson's Diseasementioning
confidence: 99%